Entre brechas e vagas noturnas: memórias de educadoras em recife nos anos ditatoriais de 1964 a 1977 - Ferreira da Silva, André Gustavo; Farias, Cassiana Maria; Silva, Thalita Grazielly (Revista Brasileira de História da Educação, 2016)
Memories of three educators in their respective social positions, in the city Recife-PE are shown in the present study. Methodologically, the insertion in the oral history is justified by the possibility of achieving the everyday perceptions, approaching the subjective creation of consensus and subjective modes in response to the coercive environment brought by Civil-Military Dictatorship. It is about the concepts of force, coercion and consensus based on Gramsci. It was concluded that among the waves of domination by the dictatorship, the educators developed deviation and resistance strategies in relation to coercion. Through the precariousness of the quotidian domination – the regime’s gaps - educators preserved the critical view on the dictatorship and performed actions directly against the supposedly hegemonic interests.